Carbon Neutrality Design for SDG#3 Wellness and #12 Responsible Production and Consumption – Case Study of ESGSCHOOLHK - Ching, Shirley Yeung Mo (Journal of Ecohumanism, 2025)
According to the definition of Brundtland Commission (1992) of the United Nations, “sustainable development is development that meets the needs of the present without compromising the ability of future generations to meet their own needs.” The basic element of sustainability in terms of ability to meet needs is to have an awareness to apply carbon neutrality design in the space usage to cater the needs of a coworking space for community events to learn how to transform with practices on SDG implementation. This is one of the United Nations Sustainable Development Goals (UNSDG) #3 and 12 – Well Being and Responsible Production and Consumption. It is suggested to implement ISO 14068-2023 Climate Change Management System for Transition to Net Zero in design of a coworking space and event planning to reinforce responsible management in workplace design with wellness and sustainable skills development.